RETRACTED: ENHANCING MANAGERIAL DECISIONS: THE ROLE OF ACCOUNTING PRACTICES AND E-COMMERCE IN MALANG'S MSMEs - Febri Yanto, Alif Faruqi; Rahmawati, Apriana (Universitas Bunda Mulia, 2024)
RETRACTED: This article has been retracted due to issues that violate the research code of ethics